Infiltrating mammary carcinoma in a cat with a congenital disorder: prognostic interest of histological examination (FAVE Sección Ciencias Veterinarias, 2022)
This report describes the handling and clinical evolution of a malignant feline mammary carcinoma (FMC) in an eight-year-old female crossbred cat with a congenital disorder. Hence, the efficacy of tumor mass removal and the case prognosis was established by postoperative routine histological examination. A 6 cm diameter lump in the left thoracic mammary gland of multinodular appearance and purulent exudate with a reddish hue was excised after the entire mastectomy. The histopathological analysis showed the presence of numerous lymphovascular tumor emboli and frequently mitotic cells with hyperchromatic nuclei. These were consistent with an aggressive malignancy with a poor prognosis explaining the patient's death within 7 weeks after surgery. Histology and cytology findings are of critical importance to clinicians in the management of the most common mammary malignancies in cats, to provide the best possible relief to animals with life-threatening cancer. It could also serve as a cancer model for advancing knowledge in congenitally affected humans.
Keywords: feline; mammary tumor; lymphatic emboli; prognosis